Accuracy of faecal immunochemical testing in patients with symptomatic colorectal cancer. Issue 6 (18th September 2020) - Khan, A. A.; Klimovskij, M.; Harshen, R.
Abstract : Background: The aim of this study was to determine the diagnostic accuracy of the faecal immunochemical test (FIT) for detecting colorectal cancer in symptomatic patients. Methods: This was a prospective study of patients with bowel symptoms. Stool samples were collected during rectal examination. The HM‐JACKarc assay (Kyowa Medex, Tokyo, Japan) was used to quantify faecal haemoglobin (Hb); positive results were those with at least 10 μg Hb/g faeces. Two‐by‐two tables and receiver operating characteristic (ROC) curve analysis were used to determine diagnostic accuracy; χ 2 and Mann–Whitney U tests were used to compare other parameters. Results: A total of 928 patients were included (M : F ratio 1 : 1·5; median age 72 (i.q.r. 64–80) years). The overall prevalence of colorectal cancer was 5·1 per cent. The FIT had sensitivity of 85·1 per cent, specificity of 83·5 per cent, positive predictive value of 22·6 per cent and negative predictive value of 99·0 per cent. ROC analysis of FIT for diagnosing colorectal cancer gave an area under the curve value of 0·89 (95 per cent c.i. 0·84 to 0·94). Significant bowel pathology was detected more frequently in FIT‐positive patients (35·1 per cent versus 7·1 per cent in FIT‐negative patients; P < 0·001). There were sex differences in FIT positivity (23·7 per cent in men versus 17·4 per cent in women; P = 0·019); the sensitivity of FIT for colorectal cancer in women was also low. False‐negative FIT results were found mainly in women referred with iron‐deficiency anaemia, who were found to have caecal cancer. Conclusion: FIT effectively excluded colorectal cancer in symptomatic patients. Integration of FIT into the diagnostic pathway for colorectal cancer would direct resources appropriately to patients with a greater likelihood of having the disease. Abstract : This study confirmed that the faecal immunochemical test (FIT) has a high diagnostic accuracy for detecting colorectal cancer in symptomatic patients. FIT can be used to triage 2‐week‐wait colorectal referrals. FIT tests to streamline pathways Abstract : Antecedentes: Determinar la precisión diagnóstica de la prueba inmunoquímica fecal ( faecal immunochemical test, FIT) para la detección del cáncer colorrectal ( colorrectal cáncer, CRC) en pacientes sintomáticos. Métodos: Se llevó a cabo un estudio prospectivo en pacientes con síntomas intestinales. Se recogieron muestras de heces durante la exploración rectal. Se utilizó el test HM‐JACKarc (Kyowa‐Medex, Japón) para cuantificar la hemoglobina fecal (f‐Hb), en la que los resultados positivos eran valores mayores o iguales a 10 μg Hb/g de haces. Se utilizaron tablas de dos por dos y el análisis de la curva del operador del receptor ( receiver operator curve, ROC) para calcular la precisión diagnóstica; las variables se compararon mediante los tests de ji‐al cuadrado y U de Mann‐Whitney. Resultados: Se incluyeron un total de 928 pacientes (V:M = 1:1, 5; mediana de edad 72 años, rango intercuartílico 64‐80). La prevalencia global de CRC fue del 5%. El FIT presentó una sensibilidad del 85, 1%, especificidad del 83, 5%, valor predictivo positivo del 22, 6% y valor predictivo negativo del 99%. El análisis de la curva ROC de FIT para el diagnóstico de CRC mostró un valor del área bajo de curva de 0, 89 (i.c. del 95% 0, 84‐0, 94, P < 0, 001). En el grupo FIT‐positivo, se detectaron un mayor número estadísticamente significativo de patologías intestinales (35, 7% versus 7%, P < 0, 001). Se observaron diferencias por sexo en la positividad de FIT (varones 23, 7% versus mujeres 17, 44%, P = 0, 019); la sensibilidad de FIT para el diagnóstico de CRC en las mujeres también fue inferior. El grupo de falsos negativos de CRC incluía principalmente mujeres que habían sido referidas con anemia ferropénica en las que se detectaron cánceres del intestino ciego. Conclusión: La prueba FIT fue efectiva para excluir a los pacientes sintomáticos con CRC. La integración de FIT en el procedimiento diagnóstico del CRC dirigiría apropiadamente los recursos a pacientes con una mayor probabilidad de presentar un CRC.